American masters. Rothko : pictures must be miraculous - Slade, Eric; Sacks, Julie (Julie A.); Oregon Public Broadcasting (Arlington, VA : Public Broadcasting Service, 2019)
Painter Mark Rothko is one of the most renowned figures of the Abstract Expressionist movement. This film explores Rothko's journey and includes interviews with his children, Academy Award-nominated writer John Logan, and many others.
Title from resource description page (viewed May 04, 2020).
In English.
Keywords: Rothko, Mark, -- 1903-1970.; Rothko, Mark, -- 1903-1970; Abstract expressionism -- United States; Painters -- United States -- Biography; Expressionnisme abstrait -- États-Unis.; Peintres -- États-Unis -- Biographies; Abstract expressionism; Painters; United States; Biographies; Documentary television programs; Documentary television programs; Documentaires télévisés.